DEPOSIT STRUCTURE CHARACTER CaCO ON THE SHELLS OF SCALLOP (Amusium pleuronectes) AS BIO-INDICATORS OF ENVIRONMENTAL CONDITIONS IN THE BATANG WATERS - Ristiawan Agung Nugroho; Pinandoyo Pinandoyo; Tristiana Yuniarti; Vivi Endar Herawati (AQUASAINS, 2017)
The objectives are :(1) Measurement of the character structure of CaCO3 deposit on simping’sshells, (2) Identifying Environmental Conditions of simping in Batang. The study will be conducted exploratory descriptive method (non-experimental).  The results showed as morphometric’s measurement, there’s no difference in the population growth of simping in Batang from 2003 to current. Based of analysis of the hue-saturation value which is the phenotype of CaCO3 biomineralization mechanism that is deposited in the shell, showed that the biological potency (early-stage) of the character of the population’s simping growth in Batang is better than the Brebes’s population as a comparison. Conditions of natural habitat in Brebes relatively better, so that CaCO3 deposits is better also.Based on those results, efforts to provide science and technology inputs to support the preservation of aquaculture activities is to engineer a better environment to support the genetic potential to convert to a more optimum growth rate.  Another thing that can do is to optimize the genetic potential of Batang’s simping as selective-breeding material in marine culture. It is expected that these strategies can be used to overcome the problem of limited production scallop in northern coast of Central Java in order to meet the needs of the market potential through mariculture activities.